An investigation of high-proficiency L2 English speakers' oral test performance: A profiling approach - Gao, Jie (Frontiers in Communication, 2022)
Linguistic profiles, which are often established through the measurement of linguistic features, are able to demonstrate characteristics shared by a specific type of text or a group of language learners. This paper examines the contexts and purposes related to profiling research in language studies, meanwhile synthesizing quantitative profiling methods such as cluster analysis, Principal Component Analysis (PCA), and Factor Analysis (FA). A profiling study of high-proficiency L2 English speakers’ test performance is also presented, which explains the profiling procedure in L2 speaking assessment. Cluster analysis conducted on speech fluency and vocabulary variables rendered four different speech profiles, which are associated with the speakers’ L1 background and L2 English proficiency level. This paper also discusses the interpretation of linguistic profiles, as well as the statistical concerns involved in the profile construction process.